2020
DOI: 10.21039/cca.32
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Women’s Culture of Silence on Sexual Violence: Perception of Babcock University’s Female Undergraduates

Abstract: The study examines the perception of female undergraduates' about the role of social media in breaking women's culture of silence on sexual violence. Violence against women is a subject of concern due to its prevalence and the culture of silence associated with it. Involvement of social media groups appears to be changing this trend as women are supported to speak out. The study examines some social media platforms involved in this campaign, how they contribute to knowledge of females and shape their attitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Throughout history, women have had to fight for equality, freedoms, and rights (Adamek, 1994; Akoja & Anjorin, 2020; Barry, 2013; Berg, 1989; Berlant, 1993; Bhattacharyya, 2018; Blumell & Mulupi, 2020; Brown, 2003; Carlin & Winfrey, 2009; Colby, 2013; Daniels, 1996; Deitch, 1993; Dolan, 2001; Foster, 2008; Fuchsman, 2017; Gantt-Shafer et al, 2019; Ginsburg, 1973; Hardouin et al, 2020; Hargis, 1955; Hebert, 2018; Houghton, 1999; Hsia, 1978; Jacoby, 1975; Kenneally, 1967; Kimble & Olson, 2006; Kitch, 2018; Lathers, 2009; Lewis, 2011; Linehan, 2017; Lunardini & Knock, 1980; Maloney, 1996; Marshall, 1986; Masel-Walters, 1976; McCammon & Brockman, 2019; McCammon & Campbell, 2001; O’Malley, 2020; Porter, 2014; Richards, 2007; Rosenthal & Peters, 2008; Rupp, 1996; Siebler, 2010; Siegle, 1985; Simon, 2002; Sorock, 2010; Sullivan, 2006; Thompson, 2002; Towns, 1966; Tyner & Ogle, 2007; Wade & Fiorentino, 2017; Wayne, 2020). As shown in Table 1 (Milligan, 2017), there are a variety of historical events, movements, and milestones that have affected and impacted women’s rights…”
mentioning
confidence: 99%
“…Throughout history, women have had to fight for equality, freedoms, and rights (Adamek, 1994; Akoja & Anjorin, 2020; Barry, 2013; Berg, 1989; Berlant, 1993; Bhattacharyya, 2018; Blumell & Mulupi, 2020; Brown, 2003; Carlin & Winfrey, 2009; Colby, 2013; Daniels, 1996; Deitch, 1993; Dolan, 2001; Foster, 2008; Fuchsman, 2017; Gantt-Shafer et al, 2019; Ginsburg, 1973; Hardouin et al, 2020; Hargis, 1955; Hebert, 2018; Houghton, 1999; Hsia, 1978; Jacoby, 1975; Kenneally, 1967; Kimble & Olson, 2006; Kitch, 2018; Lathers, 2009; Lewis, 2011; Linehan, 2017; Lunardini & Knock, 1980; Maloney, 1996; Marshall, 1986; Masel-Walters, 1976; McCammon & Brockman, 2019; McCammon & Campbell, 2001; O’Malley, 2020; Porter, 2014; Richards, 2007; Rosenthal & Peters, 2008; Rupp, 1996; Siebler, 2010; Siegle, 1985; Simon, 2002; Sorock, 2010; Sullivan, 2006; Thompson, 2002; Towns, 1966; Tyner & Ogle, 2007; Wade & Fiorentino, 2017; Wayne, 2020). As shown in Table 1 (Milligan, 2017), there are a variety of historical events, movements, and milestones that have affected and impacted women’s rights…”
mentioning
confidence: 99%
“…The increased risk of fracture and spinal nerve compression in AIS patients with osteoporosis has also been highlighted. The efficacy of 3D printed braces in immediate treatment has been demonstrated, and comparisons between Schroth exercises and proprioceptive neuromuscular facilitation have favored Schroth exercises for reducing scoliosis angle and enhancing functional capacity (19)(20)(21)(22). A pivotal study in 2020 revealed the effectiveness of spinal mobilization on Cobb's angle and respiratory function in AIS patients, where joint mobilization resulted in a notable shift in Cobb's angle (23).…”
Section: Discussionmentioning
confidence: 99%
“…One third of the individuals felt inspired to share their experiences with others. On the other hand, very important and influential people such as celebrities who have publicly spoken out about their own experience(s) with SA and SV have helped the #MeToo-debate and the awareness of SA and SV ( 44 ). Celebrities that publicly speak out about their own experiences may allow for other individuals to see them as role models.…”
Section: Discussionmentioning
confidence: 99%